Rural labor: a study of the workers on an estancia in the west of Buenos Aires province, Argentina (1866-1875) (Quinto Sol, 2025)
This article investigates some of the organizational characteristics of Estancia La Rica, located in the Chivilcoy district of Buenos Aires province, by analyzing its accounting books from 1866 to 1875. Through cross-referencing these records with a diverse bibliographic corpus, the study examines the establishment of both stable and temporary workforces, focusing on their attributes, labor categories, hiring practices, performed tasks, production relationships, and implemented strategies. Despite the inherent limitations of case studies, this research deepens the understanding of labor and production organization in a western Buenos Aires estancia during the late 19th century.
Keywords: rural history; workers; personnel management; rural economy